THEORETICAL AND METHODOLOGICAL FOUNDATIONS OF THE DIGITALIZATION OF THE ENTERPRISE WORKFORCE FORMATION PROCESS (Regional aspects of productive forces development of Ukraine, 2026)
Introduction: In modern conditions, digital transformation serves as a key factor in enhancing the competitiveness of enterprises. The rapid development of information technologies significantly impacts all aspects of business management, including HR policies. Personnel formation, which was previously a lengthy and resource-intensive process, is now being transformed by digital tools that enable the automation of recruitment, adaptation, and professional development of employees. The digitalization of HR management not only optimizes personnel selection processes but also enhances their effectiveness through data analytics and artificial intelligence. This opens up new opportunities for creating high-performance teams that meet the current demands of the business environment.Purpose of the Article: To examine the methods of digitalizing the personnel formation process in organizations and to determine the key stages of implementing digital technologies in the HR sphere, develop and describe a methodology for digitizing the process of forming the company's personnel.Research Methods: Analysis and synthesis of scientific literature, comparative analysis, economic analysis, and expert assessments.Research Results: A study was conducted on global trends in the digital transformation of human resource management. It was revealed that leading companies actively adopt automated recruitment systems, artificial intelligence for evaluating candidates, and big data analytics for forecasting employee productivity. The experiences of Google, Amazon, Microsoft, IBM, and Tesla—enterprises successfully implementing digital HR solutions—were examined. Their methods of automating hiring, training, and career management were analyzed, demonstrating improvements in HR process efficiency. The impact of digitalization on corporate costs and productivity was analyzed. It was determined that implementing modern HR technologies optimizes personnel management, improves decision-making quality, and reduces the need for administrative resources. Strategic approaches were proposed for the digitalization of human resource management, including the use of artificial intelligence, automated platforms, and data analytics tools for effective recruitment and personnel development.  A methodology for digitalizing personnel formation has been described and developed, which ensures the comprehensive use of modern information technologies at all stages of work with personnel.Conclusions and recommendations. Based on the research, strategic recommendations were formulated regarding the digital transformation of HR management. The article proposes integrating artificial intelligence, machine learning, and data analytics to enhance the efficiency of HR processes. Thus, digitalization is an essential phase in the evolution of modern HR management, contributing to greater effectiveness, cost reduction, and the establishment of a more flexible personnel management system.Keywords: digitalization, personnel, enterprise, organizational and economic mechanism, HR technologies, automation.